Indonesia’s Gastrodiplomacy for Nation Branding, Diplomatic Relations, and Tourism Promotion: A Lived Experience Approach - Rahmat Kusnedi; Willy Arafah; M. Husen Hutagalung; Saptarining Wulan; Rahmat Ingkadijaya (Asian Journal of Social and Humanities, 2026)
Indonesia has a rich and diverse culinary heritage, but Indonesia's culinary presence globally is still limited and often less prominent than the cuisines of other countries that are promoted more systematically. This gap highlights the need to explore how gastronomy can be strategically leveraged for nation branding, diplomatic relations, and tourism promotion. This research aims to analyze Indonesia’s gastrodiplomacy as a strategic instrument for tourism promotion through a lived experience approach. This research employs a qualitative phenomenological approach. Data were collected through in-depth interviews with Indonesian diaspora actors, including chefs and restaurant owners across Asia Pacific, the United States, and Western Europe. Thematic analysis was used to interpret lived experiences and identify key patterns in tourism promotion. The findings reveal that gastrodiplomacy promotes tourism through five key mechanisms: entry point awareness, cultural communication, sensory and emotional engagement, destination image formation, and visit intention. Diaspora actors play a central role as informal tourism ambassadors. Indonesian gastrodiplomacy operates as an experiential and relational process embedded in everyday practices. It significantly contributes to nation branding, diplomatic relation, and tourism promotion, although its effectiveness is constrained by limited policy integration. This research is limited to qualitative analysis and diaspora perspectives, which may not fully represent broader tourism stakeholders. Contributions: This study introduces the concept of lived gastrodiplomacy and contributes to tourism and public diplomacy literature by emphasizing experiential and bottom-up approaches to tourism promotion.